Doctoral Studies in TIS in and about Spanish America - Alpízar-Alpízar, Mildred Isabel (2023)
This article presents the findings of a bibliometric study carried out on a corpus of 108 doctoral theses in translation and interpretation studies (TIS) produced in Spanish America or with a Spanish American theme. Aspects analyzed include place, country and year of publication; the language used in the research and publication; and the researcher’s sex and academic affiliation. The results also reveal the main hubs of production by country, a high rate of women who successfully conclude their doctoral studies, and the main research topics, as well as those whose coverage is insufficient.